Культура мовлення та мовленнєвий етикет у професійній діяльності - Вінницька, Е. А. (ХНУРЕ, 2020)
The article deals with the fact that the culture of the language (in a professional direction) is a section of linguistics, which studies the norms of the language at all levels. The accuracy, consistency, pithiness of the professional language makes his speech highly cultured, flawless and exemplary. Speaking culture is the most important condition for success in professional growth.
Keywords: культурне розмаїття; українознавство; традиції; культура